The Promise of Neuroprotective Agents in Parkinson’s Disease - Potashkin, Judith; Seidl, Stacey E. (Frontiers in Neurology, 2011)
Parkinson’s Disease is characterized by loss of dopamine neurons in the substantia nigra of the brain. Since there are limited treatment options for PD, neuroprotective agents are currently being tested as a means to slow disease progression. Agents targeting oxidative stress, mitochondrial dysfunction and inflammation are prime candidates for neuroprotection. This review identifies Rasagiline, Minocycline and creatine, as the most promising neuroprotective agents for PD, and they are all currently in phase III trials. Other agents possessing protective characteristics in delaying PD include stimulants, vitamins, supplements, and other drugs. Additionally, combination therapies also show benefits in slowing PD progression. The identification of neuroprotective agents for PD provides us with therapeutic opportunities for modifying the course of disease progression and, perhaps, reducing the risk of onset when preclinical biomarkers become available.